MBO and Goal Directedness In a Hospital Context - Covaleski, Mark A.; Dirsmith, Mark W. (Academy of Management Review, 1981)
In this article, we examine the attempt of two hospitals to implement management by objectives (MBO) as a means of improving organizational planning and control. Our conclusion is that, as a goal-directed form of management technology, MBO may lead to dysfunctional decision making at the institutional level within organizations, especially those facing complex, dynamic environments. However, if viewed as a philosophy of management administered at the sub-unit level, MBO may serve as a catalytic agent for encouraging decentralized decision making and performance evaluation.